Metabolic divergence between sibling species of cichlids Pundamilia nyererei and Pundamilia pundamilia. Issue 6 (4th June 2013) - Dijkstra, P. D.; Seehausen, O.; Metcalfe, N. B.
<x xml:space="preserve">Abstract</x> This study compared Pundamilia nyererei and Pundamilia pundamilia males in routine metabolic rate (RR) and in the metabolic costs males pay during territorial interactions (active metabolic rate, RA). Pundamilia nyererei and P. pundamilia males housed in social isolation did not differ in RR. In contrast to expectation, however, P. nyererei males used less oxygen than P. pundamilia males, for a given mass and level of agonistic activity. This increased metabolic efficiency may be an adaptation to limit the metabolic cost that P. nyererei males pay for their higher rate of aggressiveness compared to P. pundamilia males. Thus, the divergence between the species in agonistic behaviour is correlated with metabolic differentiation. Such concerted divergence in physiology and behaviour might be widespread in the dramatically diverse cichlid radiations in East African lakes and may be an important factor in the remarkably rapid speciation of these fishes. The results did not support the hypothesis that higher metabolic rates caused a physiological cost to P. nyererei males that would offset their dominance advantage.